Analysis of Land Dispute Decision Letter Inyogyakarta Ptun: Number 19/G/2023/Ptun.YK - Justicia, Sheryn N.; Aksin, Rizka Alifia Kaisha; Amanullah, Muhamad Hanidar Dafa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This Administrative Court decision focuses on analysing a land dispute case in accordance with Decision Number 19/G/2023/PTUN. The case involves Mrs. SURANI/SURYANI as the plaintiff, who feels aggrieved by the issuance of the KTUN related to the transfer of Ownership Certificate (SHM) Number 11908, which was then transferred to a person named TUTWURI HANDAYANI in 2022, and the Yogyakarta Administrative Court as the defendant that issued the KTUN. The plaintiff filed an administrative appeal because she considered the KTUN to be legally flawed as it did not go through the inheritance procedure, and she wanted the KTUN to be revoked. The purpose of this study is to analyse the elements of Administrative Court Procedure Law contained in Decision Letter Number 19/G/2023/PTUN.YK, as well as to analyse whether the KTUN is proven to comply with applicable legal provisions, such as administrative procedures. The research method used is a qualitative research method that focuses on data through the contents of the above lawsuit.